Similarities between the responses to ANT‐DBS and prior VNS in refractory epilepsy. Issue 6 (8th May 2018) - Kulju, Toni; Haapasalo, Joonas; Lehtimäki, Kai; Rainesalo, Sirpa; Peltola, Jukka
Abstract: Objectives: Neurostimulation has offered new treatment options in refractory epilepsy, first with vagus nerve stimulation (VNS) and more recently with deep brain stimulation (DBS). There is a lack of previous detailed data assessing the relationship between VNS and ANT‐DBS. The aim of this study was to investigate the potential correlation between therapeutic responses to VNS and ANT‐DBS. Materials and Methods: A total of 11 patients with previous VNS therapy underwent ANT‐DBS implantation. Monthly seizure counts starting from baseline before VNS extending to long‐term DBS treatment were analyzed. The reasons for VNS discontinuation were assessed. Results: Altogether in 10 of 11 patients, the response to VNS seemed to be similar to the response to DBS therapy. Progressive response to VNS was likely to correlate with a progressive response to DBS in three of three patients. Partial response to VNS was associated with a fluctuating response pattern to DBS in two patients. Five of six nonresponders to VNS were also nonresponders to DBS. One of the VNS nonresponders obtained progressive response to DBS. Conclusions: This is the first study to evaluate in detail the effect of both VNS and ANT‐DBS in refractory epilepsy patients. There is a putative association between VNS and DBS responses suggesting the need for further studies. Abstract : A first of its kind, this study is a detailed evaluation on the effects of both VNS and ANT‐DBS in refractory epilepsy patients. Altogether, 10 of the 11 patients presented similarities in responses between the VNS and DBS therapies. There is a putative association between the VNS and DBS responses, thus further suggesting the necessity for further studies.